(untitled) (The Review of Diabetic Studies, 2025)
Objective: To compare ’Onlay’ with ’Sublay’ hernioplasty in the treatment of uncomplicated ventral hernia concerning operative time, postoperative seroma formation, drain duration, and postoperative hospital stay. Methods: Seventy-eight patients diagnosed with uncomplicated ventral hernias were retrospectively recruited to a randomized study from October 2023 to November 2024. The patients have been divided into two equal groups: Group A underwent hernioplasty with onlay mesh repair, while Group B received a sublay mesh repair. The evaluation of both methods focused on safety, efficacy, operative time, and complications. Results: Our study demonstrated no significant differences in demographic characteristics or preoperative comorbidities between the two groups. Moreover, no significant disparities were observed regarding the size of the defect [4.20±1.12 vs 4.20±1.13 cm, p=0.984] or the type of hernia [p=0.462]. Notably, operative time was significantly shorter in the Onlay Group than in the Sublay Group, with a mean duration of 49.25±11.76 minutes versus 58.90±10.10 minutes (p<0.001). Furthermore, a significant difference in drainage duration was observed: 8.08±1.77 days in the Sublay Group versus 6.56±1.37 days in the Onlay Group (p<0.001), indicating a shorter drainage period in the Sublay Group. While the differences in complication rates were not statistically significant, the Sublay Group exhibited lower complication rates than the Onlay Group. Conclusion: The Sublay technique, despite requiring longer operative time, offers significantly fewer wound complications and recurrence rates than the Onlay method, making it a more reliable and safer option for hernia repair.